A wearable, waterproof, and highly sensitive strain sensor based on three-dimensional graphene/carbon black/Ni sponge for wirelessly monitoring human motions. Issue 6 (9th January 2020) - Sun, Shibin; Liu, Yiqian; Chang, Xueting; Jiang, Yingchang; Wang, Dongsheng; Tang, Chengji; He, Shiyu; Wang, Mingwei; Guo, Lin; Gao, Yang
Abstract : A wearable, waterproof, and highly sensitive strain sensor for wirelessly monitoring human motions. Abstract : The exploration of wearable strain sensors with new characteristics and functionalities could fuel the rapid development of Internet of Things (IoT) technology for the healthcare industry. Herein, we present a flexible, waterproof, and highly sensitive strain sensor that is fabricated by integrating graphene (G), carbon black (CB), and polydimethylsiloxane (PDMS) into the three-dimensional (3D) framework of commercial Ni sponge via a simple, cost-effective, and scalable drop-coating method. The G/CB/Ni strain sensor demonstrates good flexibility, high sensitivity (gauge factor of 138 at 16% strain), and long-term stability. The G/CB/Ni sensor could not only precisely monitor subtle human motions such as pulse, blinking, and swallowing, but it also shows potential in testing muscle strength. A wireless sensor system that consists of the G/CB/Ni strain sensor, an STM32 controller, a ZigBee module, and a portable power source is assembled, which enables remote transmission of data collected from the sensor to the computer wirelessly. The G/CB/Ni sensor also exhibits excellent waterproofness and can be safely used to monitor human motions under humid conditions and in water. The G/CB/Ni strain sensor featuring flexibility, high sensitivity, and waterproofness has great potential for applications in healthcare management, personal rehabilitation training, and outdoor motion monitoring.